2021
DOI: 10.6002/ect.2021.0050
|View full text |Cite
|
Sign up to set email alerts
|

Not All Piggybacks Are Equal: A Retrospective Cohort Analysis of Variation in Anhepatic Transcaval Pressure Gradient and Acute Kidney Injury During Liver Transplant

Abstract: Objectives: Complete inferior vena cava clamping in caval replacement during liver transplant is associated with substantial physiological derangement and postoperative morbidity. Partial clamping in the piggyback technique may be relatively protective, but evidence is lacking. Having observed substantial variation in transhepatic inferior vena cava pressure gradient with piggyback, we hypothesized that the causative mechanism is the extent of caval clamping rather than the surgical approach. Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Oliver et al. measured the anhepatic inferior vena cava pressure gradient and found that it varied substantially, with pressure gradient being linearly associated with early acute kidney injury (AKI) 61 . This suggests that renal venous congestion is an etiological factor to post operative AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Oliver et al. measured the anhepatic inferior vena cava pressure gradient and found that it varied substantially, with pressure gradient being linearly associated with early acute kidney injury (AKI) 61 . This suggests that renal venous congestion is an etiological factor to post operative AKI.…”
Section: Discussionmentioning
confidence: 99%
“…This should result in the repositioning of the clamp, where it is surgically possible to do so, with potential hemodynamic benefits that are likely to impact on renal outcomes. 1 There are some specific patient groups where maintenance of unobstructed venous return throughout the transplant is of critical importance. Patients with significant diastolic dysfunction (frequently seen in cirrhotic cardiomyopathy) or obstructive pathologies, like hypertrophic obstructive cardiomyopathy or inducible systolic anterior motion of the mitral valve, are very sensitive to alterations in preload.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 This information permits adjustment of the side-biting vascular clamp to decompress the IVC if a piggyback technique has been employed, helps guide fluid management, and also identifies flow obstruction at the IVC anastomoses, which may cause graft dysfunction. We have recently shown that the TCPG during the anhepatic phase of transplant is independently associated with risk of postoperative acute kidney injury, 1 highlighting the clinical importance of this measurement and the value of IVC decompression. However, calculating the TCPG necessitates the insertion of a femoral central line for the purpose of IVC pressure assessment.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation